2010
DOI: 10.1136/tc.2009.031773
|View full text |Cite
|
Sign up to set email alerts
|

Health warning labelling practices on narghile (shisha, hookah) waterpipe tobacco products and related accessories

Abstract: BackgroundWaterpipe tobacco smoking prevalence is increasing around the globe despite current evidence that smoke emissions are toxic and contain carcinogenic compounds.ObjectiveTo evaluate current health warning labelling practices on waterpipe tobacco products and related accessories.MethodsAll waterpipe tobacco products, as well as waterpipe accessories, were purchased from Lebanon and a convenience sample was obtained from Dubai (United Arab Emirates), Palestine, Syria, Jordan, Bahrain, Canada, Germany and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 24 publications
1
91
1
1
Order By: Relevance
“…In reality, shisha smoke is just as dangerous as cigarette smoke (Knishkowy and Amitai, 2005). As compared to a single cigarette, shisha smoke contains even higher level of metals such as arsenic, lead, and nickel, 36 times more tar, 15 times more carbon monoxide and nicotine (Knishkowy and Amitai, 2005 Nakkash and Khalil, 2010). Some studies claim a session of shisha smoking produces the same levels of cotinine, a nicotine metabolite, as smoking two cigarettes daily (Neergard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In reality, shisha smoke is just as dangerous as cigarette smoke (Knishkowy and Amitai, 2005). As compared to a single cigarette, shisha smoke contains even higher level of metals such as arsenic, lead, and nickel, 36 times more tar, 15 times more carbon monoxide and nicotine (Knishkowy and Amitai, 2005 Nakkash and Khalil, 2010). Some studies claim a session of shisha smoking produces the same levels of cotinine, a nicotine metabolite, as smoking two cigarettes daily (Neergard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that GHWs should be placed on the waterpipe device itself 25,40 . Turkey has gone a step further, requiring that health warnings be placed on the waterpipe's effect that smoking status might have on the effectiveness of GHW location, our study did not aim to test different subgroups such as women and young adults.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Turkey has gone a step further, requiring that health warnings be placed on the waterpipe's effect that smoking status might have on the effectiveness of GHW location, our study did not aim to test different subgroups such as women and young adults. As WPS rates are increasing and attracting more youth and women, the effectiveness of the design, content, and position of GHWs needs to be assessed in these groups 1,17,25,45 . Our study focused mainly on the visibility of GHWs, but it did not investigate quit intention and quit attempts as a result of seeing the warnings.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The misperception that hookah tobacco is a safe non-cigarette product is perpetuated by the inaccurate labeling in which tar and nicotine levels are listed as negligible (20). In addition, hookah tobacco packages are devoid of health warning labels (21). Indeed, the full complement of hookah tobacco ingredients are unknown (22).…”
Section: Introductionmentioning
confidence: 99%